David v. Goliath: questions on the lawfulness of anticipatory self-defense (2024)
This article addresses whether there is a customary rule in international law that authorizes the use of anticipatory self-defense. The question will be addressed from a TWAIL perspective where the definition of the specially affected states takes a prevalent role in the establishment of the rule.